21 Impact of Combined Atrial Fibrillation and Heart Failure on Mortality: 14 Year Naturalistic Follow-Up Study. (3rd June 2016) - Ziff, Oliver; Carter, Paul R; McGowan, John; Chandran, Suresh; Uppal, Hardeep; Potluri, Rahul
Abstract : Background: Atrial Fibrillation (AF) and Heart Failure (HF) frequently co-exist conferring considerable morbidity and mortality, yet current treatment options remain limited. Recent meta-analyses of patients with concomitant AF and HF have suggested no prognostic benefit of beta-blockers or digoxin, creating a paradox whereby those most in need have the fewest therapeutic choices. We sought to investigate the association between HF and AF and their impact on mortality from a large 14-year naturalistic follow-up study. Methods: Anonymous data of adult patients aged ≥18 with all types of HF and AF admitted to several hospitals in the North of England between 2000 and 2013 was obtained and processed using the ACALM (Algorithm for Co-morbidity, Associations, Length of stay and Mortality) study protocol. ACALM uses the ICD-10 and OPCS-4 coding systems to identify patients and the methodology has been published widely. Analyses were performed comparing mortality between patients with HF, AF and combined HF and AF at baseline and their development during follow-up. Results: At baseline, of 929, 552 adult patients 29, 164 (3.1%) had AF, 19, 474 (2.1%) had HF, and 5, 728 (0.6%) had both HF and AF. Of those with AF at baseline, 1, 647 (5.6%) developed HF during follow-up, and of those with HF at baseline, 824 (4.2%) developed AF during follow-up. Demographics and crude mortality rates are shown; see Table . Patients with combined AF and HF at baseline had increased mortality than patients with AF or HF alone. Patients with AF at baseline that developed HF, and patients with HF at baseline that developed AF, experienced a greater mortality compared to those with combined HF and AF at baseline; see Figure . Conclusion: Concomitant AF and HF is associated with substantial mortality and risk of death, irrespective of which disease develops first. In light of limited current treatment for these patients, future therapies to specifically target the combined HF and AF group are required.